Utilization of Pervious Concrete in CO2 Capturing to Control Environmental Impact of Portland Cement - J. Alsaad, Aymen; S.al-Attar, Tareq; S. Alshathr, Basil (International Journal of Engineering and Technology, 2018)
The cement industry is a main producer of greenhouse gases that is responsible for 5–7% of CO2 emissions. Therefore, it is important to find a method to reduce the concentration of this gas in the environment especially in places such as tunnels. This work aims to use pervious concrete to capture CO2 from the environment and transform it to calcium carbonate inside its matrix. The pervious concrete exposed at 7, 14, and 28 days age to 25 and 50% concentration of CO2 for a period of 2 and 4 hours to study the extent of carbonation inside this concrete. In addition to that, the effects of carbonation on compressive strength, weight change, CO2-uptake and change in permeability were studied. The results showed that higher concentration of CO2 and longer exposure periods caused deeper penetration of carbonation. The maximum recorded CO2 uptake by pervious concrete occurs when it was exposed to higher CO2 % and longer duration of exposure at the age of 7 days.